(untitled) (Research, Society and Development, 2022)
Pyroplasmosis is a hemoparasitosis that affects domestic mammals and is caused by infection of blood cells by Babesia and Rangelia protozoa. This work deals with a case of piroplasmosis that occurred in São Paulo, SP, Brazil, where a male SRD dog, aged two years and nine months old, presented nonspecific clinical signs, but suggestive of hemoparasitosis. The patient had noted apathy and bilateral lymphadenomegaly in popliteal and femoral lymph nodes. Haematological tests revealed only thrombocytopenia. Although the patient had a negative result in the serodiagnostic tests for the detection of Babesia sp and the 4DX test to search for antibodies against Babesia sp, based on the findings of a blood smear, where it was possible to observe the presence of protozoa, the diagnosis for piroplasmosis was considered positive. The animal was treated with doxycycline for 28 days and, upon return after treatment, complete remission of the clinical picture was observed, with reestablishment of platelet levels. Although in the present report, the tutors did not accept to continue carrying out more complementary exams that could identify Rangelia sp, the authors endorse the need for more detailed investigations, in order to better differentiate the clinical conditions involving these two protozoa and also clarify with greater force the epidemiological issues of canine hemoparasitosis.